Ahlan wa Sahlan Ya Ramadhan - Fatah Yasin, Raudlotul Firdaus (Sultan Haji Ahmad Shah (SHAS) Mosque, International Islamic University Malaysia, 2017)
By performing fasting, the soul will be strengthen with self-refrain and self-control from the evil deeds towards a more purposeful life, so that people achieve intimacy and closeness with the Creator